Impact of Public Investment and its contribution to the economic development of the province of San Roman, Puno, 2007-2021 - Cano Ccoa, Dominga Micaela (2023)
The main goal of public investment is to improve the economy of the region where it is applied. However, there are several activities that have an impact on economic growth. This study investigated the impact of public investment and other economic activities on the economic development of the province of San Roman during the last 15 years, 2007 - 2021. For this purpose, statistical analyses such as ANOVA, Regression and multifactorial correlation were carried out, the results of which showed that all the variables have a significant influence on economic growth represented by the gross domestic product (GDP). The percentages in which they influence are Public Investment (PI) has an incidence of 0.35%, the economic activity of Agriculture has an incidence of 28.82%, the Manufacturing Activity 4.11% and finally, the Economic Activity of Commerce has an incidence of 63.99% on the GDP. In this sense, the factor or variable that has the greatest impact in determining the economic development of the province of San Román is not Public Investment as was presumed, but rather it is the Commerce Activity followed by the Agriculture and Manufacturing Activities. These results would be very useful to the authorities in order to modify the focus of the sectors of public investment that they have been carrying out, because the impact on economic growth is minimal. Therefore, it is necessary to change the focus of public investment in order to have more accurate results.